THE EFFECT OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON FIRM VALUE IN ENERGY SUB-SECTOR COMPANIES IN INDONESIA - Andrie Kurniawan; Bryan Givan; Devi Sofyanty; Salma Rosyidah (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to examine the effect of profitability, liquidity, and leverage on firm value in energy sub-sector companies listed on the Indonesia Stock Exchange. The research employs a quantitative approach using secondary data derived from corporate financial statements. The analysis is conducted using panel data regression to capture variations across firms and over time. The findings reveal that profitability has a positive and significant influence on firm value, indicating that companies with higher earnings performance tend to receive better market valuation. This result supports signalling theory, which suggests that strong financial performance serves as a positive signal to investors. In contrast, liquidity does not show a significant effect on firm value, implying that the ability to meet short-term obligations is not a primary consideration for investors in this sector. Similarly, leverage is found to have no significant impact on firm value, suggesting that the use of debt does not directly affect market perception in capital-intensive industries such as energy. Overall, the results highlight that profitability is the most dominant factor influencing firm value, while liquidity and leverage play a less critical role. This study contributes to the literature by providing empirical evidence from the energy sector and offers practical implications for management in enhancing firm value through improved financial performance.